The Influence of Liquidity, Firm Size, Book to Market Equity, and Market Risk on The Required Rate of Return of the Companies Listed in Indonesia Stock Exchange (IDX) Period 2016-2019 - Sadikin, Ragil Aulia (Program Pascasarjana, Universitas Riau, 2023)
The capital market is a platform for buying and selling securities, serving as an effective means to accelerate economic growth. It allows investors to make long-term investments by channeling public funds into productive sectors. When investing, investors consider two main factors: the required rate of return and risk. Rational investors seek information and perform various analyses to minimize investment uncertainty and risks. This study aims to determine the effect of liquidity, firm size, market-to-book equity, and market risk on the required return of shares. The data includes companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019, with a total sample of 264 companies consistently listed on the IDX over four years, amounting to 1,056 data points. These companies were selected through purposive sampling. The hypothesis testing methods used include the t-test, F test, coefficient of determination, and multiple linear regression analysis. The results indicate that liquidity does not affect the required rate of return in both high and low liquidity groups. Firm size affects the required rate of return in the high liquidity group but not in the low liquidity group. Book-to-market equity does not affect the required rate of return in either group. Market risk affects the required rate of return in both high and low liquidity groups.